NMR Spectroscopy in Pharmaceutical Analysis. - Holzgrabe, U. (Ulrike) (Elsevier, 2008)
Separation techniques such as high performance liquid chromatography, gas chromatography, super fluid chromatography and capillary electrophoresis techniques, govern the purity evaluation of drugs. These techniques are not always able to solve the analytical problems. This book describes the possibilities of qNMR in pharmaceutical analysis.